Randall Selitto pressure algometry for assessment of bone‐related pain in rats. (23rd July 2014) - Falk, S.; Ipsen, D.H.; Appel, C.K.; Ugarak, A.; Durup, D.; Dickenson, A.H.; Heegaard, A.M.
Abstract Background Deep pain is neglected compared with cutaneous sources. Pressure algometry has been validated in the clinic for assessment of bone‐related pain in humans. In animal models of bone‐related pain, we have validated the Randall Selitto behavioural test for assessment of acute and pathological bone pain and compared the outcome with more traditional pain‐related behaviour measures. Methods Randall Selitto pressure algometry was performed over the anteromedial part of the tibia in naïve rats, sham‐operated rats, and rats inoculated with MRMT‐1 carcinoma cells in the left tibia, and the effect of morphine was investigated. Randall Selitto measures of cancer‐induced bone pain were supplemented by von Frey testing, weight‐bearing and limb use test. Contribution of cutaneous nociception to Randall Selitto measures were examined by local anaesthesia. Results Randall Selitto pressure algometry over the tibia resulted in reproducible withdrawal thresholds, which were dose‐dependently increased by morphine. Cutaneous nociception did not contribute to Randall Selitto measures. In cancer‐bearing animals, compared with sham, significant differences in pain‐related behaviours were demonstrated by the Randall Selitto test on day 17 and 21 post‐surgery. A difference was also demonstrated by von Frey testing, weight‐bearing and limb use tests. Conclusion Our results indicate that pressure applied by the Randall Selitto algometer on a region, where the bone is close to the skin, may offer a way to measure bone‐related pain in animal models and could provide a supplement to the traditional behavioural tests and a means to study deep pain.